MEKANISME KETAHANAN KAKAO BERMIKORIZA TERHADAP CEKAMAN KEKERINGAN DAN GANGGUAN PENYAKIT - DHARMA F, AGUSDIN ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Cocoa is one of the plantation commodities which its role is quite important for the national economy, provide employment, income and foreign exchange, thus cocoa has good prospects for development of cultivation. However, the cultivation of cocoa on large scale is faced with the problem of limitation of water, especially on marginal lands caused drought stress on cocoa. In addition to drought, diseases may also lead to low productivity of cocoa. Therefore, it is necessary arbuscular mycorrhizal fungi (AMF) to increase resistance of cocoa to drought and diseases, because AMF has known helping plant to water absorption and synthesis induction of defense compound against pathogen infection. This research aimed to study the effect of AMF to the growth and resistance of cocoa in the field on drought stress, as well as mechanism of AMF to increase resistance against diseases. The experiment was carried out in the field with the AMF inoculation and fertilization treatment using different doses. Results showed the cocoa in field inoculated by AMF had better growth than cocoa without inoculation and could avoid to drought stress by maximalization of water absorption in minimum soil water condition so as to maintain the relative water content of leaf at level of more than 70%. AMF inoculation could decrease anthracnose leaf spot disease intensity caused by Colletotrichum gloeosporioides amounted to 16.39%, caused to more equitable lignification on cocoa root cortex tissue so as could increase cocoa defense to drought stress, but had no direct effect on the accumulation of salicylic acid and flavonoid in the cocoa.